2015
DOI: 10.1007/s11356-015-4480-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of three classes of integrons in antibiotic-resistant bacteria isolated from Jiulong River in southern China

Abstract: We identified antibiotic-resistant bacterial isolates from the surface waters of Jiulong River basin in southern China and determined their extent of resistance, as well as the prevalence and characterization of three classes of integrons. A phylogenetic analysis of 16S ribosomal DNA (rDNA) sequences showed that 20 genera were sampled from a total of 191 strains and the most common genus was Acinetobacter. Antimicrobial susceptibility testing revealed that the 191 isolates were all multiresistant and there wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The present results corroborate the findings of other authors who reported on the dominance of the int I1 gene among integrase-encoding genes in environmental samples [ 67 ]. Integrons are ubiquitous in TWW [ 25 , 32 , 68 , 69 ] and in rivers such as the Vistula, Warta, and Łyna [ 29 , 60 , 70 , 71 ]. These genetic structures promote rapid bacterial evolution by enabling bacteria to accumulate, express, and transfer coding sequences such as ARGs [ 67 , 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…The present results corroborate the findings of other authors who reported on the dominance of the int I1 gene among integrase-encoding genes in environmental samples [ 67 ]. Integrons are ubiquitous in TWW [ 25 , 32 , 68 , 69 ] and in rivers such as the Vistula, Warta, and Łyna [ 29 , 60 , 70 , 71 ]. These genetic structures promote rapid bacterial evolution by enabling bacteria to accumulate, express, and transfer coding sequences such as ARGs [ 67 , 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…A. hydrophila strain MX16A was isolated from Jiulong River, Fujian, China ( Lin et al., 2015 ), and cultured with Luria-Bertani broth (Hopebio, Qingdao, China) at 30 °C in a shaking incubator for 24 h. In previous experiments, MX16A was found to be insensitive to a variety of antibiotics, and contain various resistance genes and virulence genes detected by PCR.The toxicity tests showed that the median lethal concentration (LD50) of A. hydrophila MX16A to zebrafish was 1.6×10 6 CFU/fish, indicating that MX16A had pathogenicity to aquatic animals. Antimicrobial susceptibility testing was performed using the Kirby-Bauer disk diffusion method (OXOID, UK).…”
Section: Methodsmentioning
confidence: 99%